Molecular glues of the regulatory ChREBP/14-3-3 complex protect beta cells from glucolipotoxicity - Katz, Liora S.; Visser, Emira J.; Plitzko, Kathrin F.; Pennings, Marloes A. M.; Cossar, Peter J.; Tse, Isabelle L.; Kaiser, Markus; Brunsveld, Luc; Ottmann, Christian; Scott, Donald K. (Nature communications, 2025)
The Carbohydrate Response Element Binding Protein (ChREBP) is a glucose-responsive transcription factor (TF) with two major splice isoforms (α and β). In chronic hyperglycemia and glucolipotoxicity, ChREBPα-mediated ChREBPβ expression surges, leading to insulin-secreting β-cell dedifferentiation and death. 14-3-3 binding to ChREBPα results in cytoplasmic retention and suppression of transcriptional activity. Thus, small molecule-mediated stabilization of this protein-protein interaction (PPI) may be of therapeutic value. Here, we show that structure-based optimizations of a ‘molecular glue’ compound led to potent ChREBPα/14-3-3 PPI stabilizers with cellular activity. In primary human β-cells, the most active compound retained ChREBPα in the cytoplasm, and efficiently protected β-cells from glucolipotoxicity while maintaining β-cell identity. This study may thus not only provide the basis for the development of a unique class of compounds for the treatment of Type 2 Diabetes but also showcases an alternative ‘molecular glue’ approach for achieving small molecule control of notoriously difficult to target TFs. Targeting transcription factors with small molecules remains a significant challenge in drug discovery. Here, the authors present a structure-based approach to stabilize ChREBPα/14-3-3 interactions, suppressing ChREBPβ and protecting β-cells from glucolipotoxicity, showcasing ‘molecular glues’ as tools to control difficult to target transcription factors.